PENGARUH UKURAN, PERTUMBUHAN DAN UMUR OBLIGASI PERUSAHAAN TERHADAP PERINGKAT OBLIGASI - Rianto; Herman Felani; Ameilia Damayanti (FEB-UP Press, 2021)
This study aims to determine the effect of variable size companies , growth companies and maturity against bond rating service sector listed in BEI 2015-2019 period. The population in this study is bond property and real estate companies listed in BEI 2015-2019 period totaling 7 companies. The sampling technique used was purposive sampling. Technical analysis of the data used is the logistic regression analysis with the help of SPSS 17 for windows. Results of the analysis showed that the partial significant effect on the bond ratings, the company's growth is not effect on the bond rating, the maturity is not effect on the bond rating Keywords: rating bonds,size, growth, and maturity